Force Sensors Using the Skew-Ray-Probed Plastic Optical Fibers - George Y. Chen; Soroush Shahnia; Tanya M. Monro; David G. Lancaster (IEEE Photonics Journal, 2018)
Simple optical force sensors have many uses but suffer from relatively low sensitivity or low fabrication-tolerance. We have demonstrated that pure skew rays can enhance the sensitivity of a bend-loss-based force sensor over the mixture of rays created from a normal incidence by a factor of 3.8 to enable a sensitivity of 0.126 dB/N. The dynamic range was measured from 222.2 mN to >14.1 N. The response/recovery times were found to be 500 and 600 ms, respectively. We also showed a compression-loss-based force sensor exhibiting a small deviation of 6.7% in sensitivity of 0.015 dB/N against the changes in the launch angle of light. The dynamic range was tested from 875.0 mN to >24.2 N. The response/recovery times were observed as 350 and 300 ms, respectively. The sensitivity of these force sensors can be further enhanced with geometry and fiber-material changes, and the enhancement technique could be extended to other designs.